ADA position statement on diabetic neuropathy. Issue 4 (2nd May 2017) - Chaplin, Steve
Abstract : The American Diabetes Association (ADA)'s recent position statement provides a useful summary of the current evidence on the prevention and management of diabetic neuropathy.